Relationship between hyperthyroidism and pulmonary function tests in female patients - Alkinany , Azza Sajid Jabbar (University of Thi-Qar Journal of Science, 2019)
This is a comparative study carried out into two groups of females of age range 25-60years:20 healthy and 21 female patients with hyperthyroidism group, who were attending Alsadar teaching outpatient hospital, Basra City, Iraq. The aim of this study was to determine the effect of hyperthyroidism on the pulmonary function tests. Pulmonary function tests such as FEV1, FVC, FEV1%, PEF and estimated lung age were all measured for all subjects involved in this study .The measurements were done by using a Spirolab III spirometer. It’s found highly significant declines (p<0.01) in FEV1, FVC and FEV1% in hyperthyroid female patients .While there was a significant decline in PEF at the level 0.05 of significance. The estimated lung age showed highly significant increase (p<o.o1) of the hyperthyroid females compared to the healthy females. Hyperthyroid females showed deterioration in all studied lung function tests.